2012
DOI: 10.4028/www.scientific.net/amm.174-177.2160
|View full text |Cite
|
Sign up to set email alerts
|

Investigation in Rural Buildings’ Damage Caused by Local Strong Wind in Suihua

Abstract: In May 15th 2010, a strong wind occurred in Suihua, which caused severe damage of building. In order to get information about damage of buildings caused by strong wind, an investigation was conducted in May 18th 2010. Through observing and interviewing, the first-hand information on the damage of rural buildings subjected to local strong wind were got. Combined with the investigation results after the disaster, an introduction to the hazard around the local strong wind region in Suihua is reported. For half-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have shown that residential buildings in rural areas have less resilience and are easily damaged during severe natural hazards. Xie et al [ 34 ] investigated rural buildings damaged by a strong wind, revealing that rural houses were highly vulnerable to strong wind events. Zaini et al [ 35 ] found that rural houses were more vulnerable during windstorm events because they had lower engineering standards.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that residential buildings in rural areas have less resilience and are easily damaged during severe natural hazards. Xie et al [ 34 ] investigated rural buildings damaged by a strong wind, revealing that rural houses were highly vulnerable to strong wind events. Zaini et al [ 35 ] found that rural houses were more vulnerable during windstorm events because they had lower engineering standards.…”
Section: Introductionmentioning
confidence: 99%